India’s Position in Mobile Computing Technology - V. Basil Hans (International Journal of Mobile Computing Technology, 2025)
India has emerged as a significant player in the global mobile computing technology landscape, driven by its large, tech-savvy population, rapidly growing digital economy, and government initiatives promoting digital transformation. The country has become one of the world's largest smartphone markets, fostering innovation and adoption of advanced mobile technologies such as 5G, AI, and IoT. Indian startups, alongside global technology giants, are contributing to advancements in mobile applications, cloud computing, and mobile-based services. Key factors such as affordable mobile devices, extensive mobile internet penetration, and digital literacy programs have enabled a surge in mobile computing usage across sectors, including healthcare, education, fintech, and e-commerce. The "Digital India" and "Make in India" initiatives by the Government of India have significantly boosted local manufacturing, application development, and the growth of homegrown technologies. However, challenges remain in bridging the rural-urban digital divide, enhancing cybersecurity measures, and fostering research in cutting-edge areas like quantum computing and mobile AI. India's future trajectory in mobile computing technology holds immense potential, positioning it as a global leader in the digital age. This study explores India's current standing in mobile computing, key technological advancements, market trends, and the challenges and opportunities ahead for sustained growth and innovation in the sector.
Keywords: 5G; Internet of things (IoT); artificial intelligence; communication; mobile technology